Increased incidence of chronic lung disease and respiratory sequelae in growth restricted versus appropriately grown preterms - Sehgal, Kartik; Sehgal, Kunal; Tan, Kenneth (Indian Journal of Child Health, 2021)
Background: Fetal growth restriction (FGR) affects 5–10% term gestational age pregnancies. When accompanied by prematurity, FGR infants have significantly greater risk of perinatal morbidity and/or mortality compared to non-growth restricted preterm infants. Aim: Current study aimed to ascertain the incidence FGR among premature infants and its association with respiratory morbidity. Methods: Institution database for preterm infants of 23–31+6 weeks of gestation was accessed. FGR infants were compared with gestation/sex matched appropriately grown infants. Results: During the period 2016–2018, 973 infants between 23 and 31+6 weeks gestation were admitted amongst whom, 206 (27%) were FGR. Between 28 and 31+6 weeks gestation, approximately 1/3rd were FGR. Gestation and birth weight of the FGR and appropriately grown cohorts were 30.2±0.2 versus 30.1±0.2 weeks (p=0.8) and 1132±43 versus 1499±54 g (p<0.0001), respectively. While antenatal steroids, surfactant, mechanical ventilation, sepsis, and ductal therapy were comparable, respiratory outcomes were significantly worse in the FGR cohort (duration of respiratory support: 37±10 vs. 23±5 days [p=0.016], home oxygen: 24 [11.6%] vs. 8 [3.8%]; [p=0.005] and chronic lung disease [CLD]: 53 [25.7%] vs. 28 [13.6%], [p=0.002], respectively). The odds ratio (95% confidence intervals) for developing CLD and for home oxygen when born FGR were 2.2 (1.3–3.6) and 3.2 (1.4–7.4), respectively. Conclusions: In spite of comparable postnatal variables, FGR infants had significantly greater respiratory morbidity.